2019
DOI: 10.1177/0883073819870944
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Outcomes of Aicardi Goutières Syndrome

Abstract: Aicardi Goutières syndrome is a monogenic interferonopathy caused by abnormalities in the intracellular nucleic acid sensing machinery ( TREX1, RNASEH2A, RNASEH2B, RNASEH2C, SAMHD1, ADAR1, or IFIH1). Most individuals affected by Aicardi Goutières syndrome exhibit some degree of neurologic impairment, from spastic paraparesis with relatively preserved cognition to tetraparesis and severe intellectual disability. Because of this heterogeneity, it is important to fully characterize the developmental trajectory in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
59
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 48 publications
(63 citation statements)
references
References 17 publications
(21 reference statements)
4
59
0
Order By: Relevance
“…Aicardi-Goutières Syndrome (AGS) is a monogenic leukodystrophy with pediatric onset, clinically characterized by a variable degree of neurologic impairment (Adang et al 2020a). It is due to mutations in genes involved in the intracellular nucleic acid sensing machinery (TREX1, RNASEH2A, RNASEH2B, RNASEH2C, SAMHD1, ADAR1, IFIH1, LSM11 or RNU7-1) that result in an abnormal overproduction of interferon alpha (IFN alpha), a mechanism shared by a group of condition now called type I interferonopathies (Livingston and Crow 2016;Uggenti et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Aicardi-Goutières Syndrome (AGS) is a monogenic leukodystrophy with pediatric onset, clinically characterized by a variable degree of neurologic impairment (Adang et al 2020a). It is due to mutations in genes involved in the intracellular nucleic acid sensing machinery (TREX1, RNASEH2A, RNASEH2B, RNASEH2C, SAMHD1, ADAR1, IFIH1, LSM11 or RNU7-1) that result in an abnormal overproduction of interferon alpha (IFN alpha), a mechanism shared by a group of condition now called type I interferonopathies (Livingston and Crow 2016;Uggenti et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In a few cases, specific pathogenic mutations in ADAR or TREX1 were inherited in the autosomal dominant manner ( 9 ). It was currently reported that TREX1 and RNASEH2B were most common among the seven pathogenic genes, accounting for 17 and 35%, respectively ( 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…We identified 17 skills from the Denver Developmental Screening Test II (DDST-II) to assess acquisition of developmental milestones in the TUBB4A-related leukoencephalopathy population (Supplemental Table S2), as previously applied in the leukodystrophy population. 18 The age at acquisition and loss of milestones was obtained from historical medical records. Information was extracted from medical records synchronous with the time of acquisition and loss of a specific milestone when feasible to minimize recall bias.…”
Section: Data Extraction and Collectionmentioning
confidence: 99%
“…These heat maps display the ages at which a given percentiles of the cohort achieved a milestone (p10 for 10%, p25 for 25% etc.). 18 Additionally, the milestone status for each individual was divided into the categories of: not yet achieved, achieved, and lost. These milestone categories were assigned to each individual at 1-month intervals to tract the transition between each category.…”
Section: Developmental Heat Maps and Developmental Function In Cohort Groupsmentioning
confidence: 99%